Subregional Structural Alterations in Hippocampus and Nucleus Accumbens Correlate with the Clinical Impairment in Patients with Alzheimer’s Disease Clinical Spectrum: Parallel Combining Volume and Vertex-Based Approach - Nie, Xiuling; Sun, Yu; Wan, Suiren; Zhao, Hui; Liu, Renyuan; Li, Xueping; Wu, Sichu; Nedelska, Zuzana; Hort, Jakub; Qing, Zhao; Xu, Yun; Zhang, Bing (Frontiers in Neurology, 2017)
Deep grey matter structures are associated with memory and other important functions, which were typically impaired in Alzheimer’s disease (AD) and its preclinical stage of mild cognitive impairment (MCI). However, systemically characterizing the subregional atrophy and deformations in these structures in AD and MCI still need more investigations. In this paper, we combined complex volumetry- and vertex-based analysis to investigate the pattern of subregional morphological alterations in deep grey matter structures and its association with clinical assessment scores in AD (n = 30) and MCI patients (n = 30). Among all 7 pairs of structures, compared with normal controls, the bilateral hippocampi and nucleus accumbens (NAc) showed significant atrophy in AD (p < 0.05). But only the atrophy in the dorsal-medial part of the left hippocampus, the ventral part of right hippocampus and the left NAc, the posterior part of the right NAc correlated with the worse clinical rating scales (p < 0.05). Furthermore, the medial-ventral part of right thalamus significantly shrank and correlated with cognition level without decreasing in its whole volume (p > 0.05). In conclusion, the degeneration of these four subregions in bilateral hippocampi and NAc resulted in severe cognition decline of patients, which might be potential target regions of treatment in preclinical AD. The surface analysis could provide additional information to volume comparison in finding the early pathological progress in deep grey matter structures.